Reducing Blood Pressure with Slow Stroke Back Massage and Warm Water Foot Soak on Isolated Systolic Hypertension Patients - Joko Sapto Pramono; Arsyawina; Isti Khomatul Masita (International Journal of Nursing and Health Services (IJNHS), 2021)
Hypertension is a non-communicable disease that caused 64% of deaths globally and in Indonesia ranks fourth of death. Management of hypertension aims to keep blood pressure within normal limits, improve the health and quality of life and reduce the risk of serious complications, including heart disease and stroke. This study aimed to determine the effectiveness of slow stroke back massage techniques and warm water foot soak in reducing systolic blood pressure. The design in this study was a quasi-experiment with a non-equivalent pre-test and post-test design without a control group. The research sample was 30 respondents taken by purposive sampling divided into two intervention groups, each of 15 respondents. Data analysis used an Independent t-test and paired t-test. The results showed an effect of slow stroke back massage and warm water foot soak intervention on reducing systolic blood pressure with p-value = 0.001 (<? = 0.05). While the independent t-test obtained a p-value = 0.057 (>? = 0.05), which means there was no difference in effectiveness between the two interventions. It was concluded that the intervention of slow stroke back massage techniques and warm water foot soak affected reducing systolic blood pressure, and both had the same effectiveness in reducing systolic blood pressure. It is recommended that community health practitioners implement slow stroke back massage and warm water foot soak as an alternative to non-pharmacological therapies for hypertensive sufferers.